Prevalence of enteroaggregative Escherichia coli among children with gastroenteritis in the northwest of Iran - mohammad Ahangarzadeh Rezaee; Gholamhassan Shahbazi; Alka Hasani; Mohammad Asgharzadeh; Ali Akbar Rahim-Rahimi; Masoud Alebouyeh (Journal of Analytical Research in Clinical Medicine, 2015)
Introduction: To investigate the prevalence of enteroaggregative Escherichia coli (EAEC) in children < 10 years with a diagnosis of gastroenteritis by multiplex polymerase chain reaction (MPCR). Methods: A total of 303 diarrheal stool samples from patients admitted to Tabriz children¢s hospital (the referral center in East Azerbaijan province of Iran) with diagnosis of gastroenteritis were enrolled in cross-sectional study for detection of three virulence genes using MPCR. Results: EAEC infection was found in 55 cases (18.2%). aspU gene was the most frequently detected gene (51 of 55). Of 55 EAEC 27 (49.1%) had only aspU gene, 4 (7.3%) just pCVD432 gene and 24 (43.6%) samples had both genes (aspU and pCVD432) simultaneously. There was no sample harboring aggR gene. Prevalence of EAEC among girls and boys were 14.6% (18/123) and 20.5% (37/180), respectively. Prevalence of EAEC according to the age group was 17% for 0-5 years (42 of 247) and 23.2% for 5-10 years (13 of 56). There was no significant association between prevalence of EAEC and the age groups and also the gender of the patients (P > 0.05). Conclusion: The present study revealed the high prevalence of EAEC in children with diarrhea in this region that should be more considered in preventing, diagnosis and treatment strategies. We conclude that using multiple virulence genes simultaneously for detection of this strain is necessary to gain reliable results with pointing to aspU as preferred gene for detecting EAEC when diagnosis based on the presence of one virulence marker. To the best of our knowledge, this is the first report on the prevalence of EAEC strains in the northwest of Iran.